1983
DOI: 10.1002/jso.2930230205
|View full text |Cite
|
Sign up to set email alerts
|

Palliative resection in gastric cancer

Abstract: Fifty-one of 256 patients underwent a palliative procedure for advanced carcinoma of the stomach (TNM stage IV). The resection was classified as palliative if metastatic disease was left behind in the lymph nodes, if involvement of organs elsewhere in the abdominal cavity was present, or if microscopy revealed tumor tissue in the resection lines. Twenty-six patients underwent a resection for palliation. There were 14 total and 12 partial gastrectomies. There were 2 deaths after total gastrectomy because of ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
6

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 9 publications
1
26
0
6
Order By: Relevance
“…In fact, improved survival was observed in pa tients with resected métastasés [2,13]. It also appears that when gastric resection is the elected procedure, then subtotal gastric resection is to be preferred since it is associated with less operative mortality and better long term survival compared to total gastrectomy [3,6,8,14]. Both the modest improvement in median survival and the occasional long-term surviving patient observed af ter noncurative surgery justify its application in a wellselected patient population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, improved survival was observed in pa tients with resected métastasés [2,13]. It also appears that when gastric resection is the elected procedure, then subtotal gastric resection is to be preferred since it is associated with less operative mortality and better long term survival compared to total gastrectomy [3,6,8,14]. Both the modest improvement in median survival and the occasional long-term surviving patient observed af ter noncurative surgery justify its application in a wellselected patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Noncurative surgical procedures for primary ad vanced gastric cancer are associated with a high inci dence of postoperative mortality [1,6,7,10]. Unfortu nately, the many variables that play an important role in the outcome of noncurative resection have not been well defined and there are no well-established guidelines for surgeons [3,8,11,12], Of 550 patients with primary gastric cancer present ing in an 18-year period, 274 (49.8%) underwent noncu rative surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1983, Meijer et al [13]from the Free University Hospital, Amsterdam reported on 51 patients who underwent a palliative procedure for advanced carcinoma of the stomach. Twenty-six of these patients underwent a palliative resection.…”
Section: Rationale For Palliative Gastrectomy In Patients With Carcinmentioning
confidence: 99%
“…Most of our patients with advanced disease are traditionally candidates for 'pallia tion' comprising either resection or a bypass procedure. The aim of palliative surgery is to improve the quality of life without producing new symptoms or incurring excess mortality or morbidity, and for some patients even to pro long comfortable survival [12], Several studies show that only tumor resection offers such potentials in patients with symptomatic disease [2,8,[13][14][15][16]. However, in many patients resection is technically impossible to per form, and the only treatment option for a tumor causing stenosis might be a gastroenterostomy or some endoscop ic procedure.…”
Section: Introductionmentioning
confidence: 99%